Circadian Rhythm Modulation of Microbes During Health and Infection - Pearson, James Alexander; Voisey, Alexander Christopher; Boest-Bjerg, Kathrine; Wong, F. Susan; Wen, Li (Frontiers in Microbiology, 2021)
Circadian rhythms, referring to 24-hour daily oscillations in biological and physiological processes, can significantly regulate host immunity to pathogens, as well as commensals, resulting in altered susceptibility to disease development. Furthermore, vaccination responses to microbes have also shown time-of-day-dependent changes in the magnitude of protective immune responses elicited in the host. Thus, understanding host circadian rhythm effects on both gut bacteria and viruses during infection is important to minimize adverse effects on health and identify optimal times for therapeutic administration to maximize therapeutic success. In this review, we summarize the circadian modulations of gut bacteria, viruses and their interactions, both in health and during infection. We also discuss the importance of chronotherapy (i.e. time-specific therapy) as a plausible therapeutic administration strategy to enhance beneficial therapeutic responses.